Proptosis in Adult Onset of Unilateral High Myopia Patient : A Case Report: Poster Presentation - Case Report - General practitioner - Marcellina; Yoseph Siahaan (Majalah Oftalmologi Indonesia, 2023)
Introduction : Unilateral high myopia is an uncommon refractive condition, because two eyes typically grow bilaterally by the same amount and resulting in symmetric myopia. Proptosis can appeared due to high axial length in myopia. Case Illustration : A 41-year-old female patient complain protruding eyeball in her left eye, gradually decrease vision, eye discomfort, and headache in her left eye since last year. There was no family history of eye disease, trauma or mass. On examination, her left eye was proptotic 3mm, best corrected visual acquity (BCVA) was 6/21 with -10.00 Sphere, and high intraocular pressure 23 mmhg. Her right eye BCVA 6/6 with -2.75 Sphere, other within normal limits. Her fundus examination showed features of high myopia and B-scan ultrasonographic showed different in axial lengths in both eyes. Orbita computerized tomography non contrast confirmed enlarge globe to posterior and proptotic in left eye. Discussion : Unilateral high myopia developing in adult onset is a rare case. It appears to be a progressive condition that have a variable age of onset. Amblyopic eye, high intraocular pressure and proptosis demonstrated as the symptoms of unilateral high myopia in this patient. Left eye proptosis confirmed by CT orbita appears secondary due to elongation anteroposterior of the globe / changesin axial components of the eye. Conclusion : High myopia can be a consideration of proptotic eye beside of mass/ tumor. Several studies to investigate patients with unilateral high myopia should be done to know the etiology and progression of the disease, thus can achieve good treatment and visual outcomes for patient.